2015
DOI: 10.1016/j.cemconcomp.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Design of polymeric capsules for self-healing concrete

Abstract: Up to now, glass capsules, which cannot resist the mixing process of concrete, have been mostly used in lab-scale proof-of-concept to encapsulate polymeric agents in selfhealing concrete. This study presents the design of polymeric capsules which are able to resist the concrete mixing process and which can break when cracks appear. Three different polymers with a low glass transition temperature T g have been extruded: Poly(lactic acid) (PLA) (T g = 59 °C), Polystyrene (PS) (Tg = 102 °C) and Poly(methyl methac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
122
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(123 citation statements)
references
References 27 publications
1
122
0
Order By: Relevance
“…Currently, numerous materials have been developed for the repairing of concrete cracks, which range in their compositions from polymer-based adhesives or healing agents [14][15][16][17][18], cementitious grouting materials [19][20][21][22], bituminous binder and sealant [23,24], electrolyte solutions [25][26][27] to more recently developed bio-based agents [28,29]. However, due to the complexity of concrete cracks and the existing discrepancies in compatibility between the repairing material and concrete substrates, re-openings of the structure after being repaired are still inevitable [10,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, numerous materials have been developed for the repairing of concrete cracks, which range in their compositions from polymer-based adhesives or healing agents [14][15][16][17][18], cementitious grouting materials [19][20][21][22], bituminous binder and sealant [23,24], electrolyte solutions [25][26][27] to more recently developed bio-based agents [28,29]. However, due to the complexity of concrete cracks and the existing discrepancies in compatibility between the repairing material and concrete substrates, re-openings of the structure after being repaired are still inevitable [10,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…It starts from the micro-cracks initiated by the repeated external loadings, and then these micro-cracks are merged into macro-cracks as a consequence of accumulation and coalescence of micro-cracks. Macrocracks provide an easy path for the transportation of water, gases, and other damaging substances into the internal structure, leading to the accelerated deterioration [2]. To prolong the service life of asphalt pavement, measures should be taken to prevent the cracks from becoming too large.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have also attempted to develop tubular polymeric capsules to carry the healing agent. Hilloulin et al [5] investigated the potential of using brittle polymeric materials with a relatively low glass transition temperature (Tg) as protection materials in self-healing concrete and found that the capsule survival probability could be improved if the capsules were heated (above Tg) prior to mixing. Gruyaert et al [6] explored the use of ethyl cellulose capsules containing different plasticizers to increase the survival of the capsules during concrete mixing.…”
Section: Introductionmentioning
confidence: 99%